(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
This writing proposes to analyze two Argentine teachers from between centuries (XIX-XX) as agents of knowledge production and social transformation in spite of the domestic stereotype that characterized teaching since its beginning. For this, their militancy practices are studied, understanding them as first expressions of a social feminism that was looking for equal rights and was based on the work exercise. Specifically, are considered documentary types that tell us about the normal teachers Sara Amaya (1881-1960) and Lola Salinas B. de Bourguet (1876-1939). In the reconstruction of their biographies and the study of their educational trajectories, we identify, even with divergences, meeting points in the postures of agency to the instituted social order of both teachers.The analysis of their participation within the political / pedagogical field contributes to the sociocultural history of education of / with women from a gender perspective since it allows a more complex reading of the group of Argentine teachers between centuries to be developed.